Analysis of the Automated Battle Injury Treatment Model Based on the Battle Injury Survival Chain - Liu, Fen; Wang, Ziqiong; Yang, Yuxia; Liu, Weili; Qiao, Yan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
This paper explores an intelligent response framework for battle injury treatment by revealing the bottlenecks and efficiency barriers in battlefield rescue response. It aims to achieve seamless coordination and maximum effectiveness of the treatment process in real combat scenarios. The concept of an automated battle injury survival chain is analyzed, and its components are demonstrated. The integration of sensing devices, communication networks, and big data analysis is discussed to support an instant decision-making support system on the battlefield. An evaluation standard is established to assess the effectiveness of the automated survival chain model.